Localisation and identification of fatigue matrix cracking and delamination in a carbon fibre panel by acoustic emission. (1st June 2015) - Crivelli, Davide; Guagliano, Mario; Eaton, Mark; Pearson, Matthew; Al-Jumaili, Safaa; Holford, Karen; Pullin, Rhys
Abstract: Background: The use of Acoustic Emission (AE) as a Structural Health Monitoring (SHM) technique is very attractive thanks to its ability to detect not only damage sources in real-time but also to locate them. Methods: To demonstrate the AE capabilities on known damage modes, a carbon fibre panel was manufactured with cut fibres in a central location and subjected to fatigue loading to promote matrix cracking. Subsequently, a delamination was created within the panel using an impact load, and the test was continued. Results: AE signals were located within the crack area in the first part of the test. After impact, AE signals were detected from both areas under fatigue loading; signals from this area were located and used for further analysis with the neural network technique. Conclusions: The application of an unsupervised neural network based classification technique successfully separated two damage mechanisms, related to matrix cracking and delamination. The results obtained allowed a more detailed understanding of such sources of AE in carbon fibre laminates.